1994
DOI: 10.1017/s088571560001410x
|View full text |Cite
|
Sign up to set email alerts
|

Application of the overlap integral in X-ray diffraction powder pattern recognition

Abstract: Use of the overlap integral in X-ray diffraction (XRD) powder pattern recognition of crystalline materials is presented. The mathematical expression, derived specifically for diffraction data, provides a measure of similarity between two patterns. Each pattern is represented by a normalized mathematical function. The index of similarity, or overlap integral, indicates how faithfully the two functions overlap and ranges from zero to unity, reaching the latter limit when the two patterns become identical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the present article, it is shown that there is a simple relationship between the conventional criterion based on squared differences, the Pearson product‐moment correlation coefficient2 and the overlap integral described by Lawton and Bartell3—who define a measure for the similarity of powder diffraction patterns on an absolute scale—when these criteria are written in terms of the correlation function. With respect to the correlation function, the drawback of these criteria is that they only consider one point (the value at the origin) from the auto‐ and crosscorrelation functions and neglect the information that is present in the remainder of the auto‐ and crosscorrelation functions.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the present article, it is shown that there is a simple relationship between the conventional criterion based on squared differences, the Pearson product‐moment correlation coefficient2 and the overlap integral described by Lawton and Bartell3—who define a measure for the similarity of powder diffraction patterns on an absolute scale—when these criteria are written in terms of the correlation function. With respect to the correlation function, the drawback of these criteria is that they only consider one point (the value at the origin) from the auto‐ and crosscorrelation functions and neglect the information that is present in the remainder of the auto‐ and crosscorrelation functions.…”
Section: Introductionmentioning
confidence: 84%
“…The Pearson product‐moment correlation coefficient is closely related to the overlap integral S αβ that is described by Lawton and Bartell 3. In principle, the method they propose is based on peak positions (lines) deduced from powder diagrams.…”
Section: Pointwise Similarity and Dissimilarity Criteriamentioning
confidence: 99%
“…A further advantage of powder-based indices is that they identify structurally related compounds (conformational phases, isomorphous systems) as similar. 26 De Gelder et al's powder-based index using cross-correlation functions, 26 based on similar previously proposed measures, [31][32][33] is a very popular powder-based index. 19,[34][35][36][37][38] Comparing an in silico crystal structure with an experimental pattern using a powder-based index requires overcoming two difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of different similarity measures depends on the characteristics of the spectra that are being evaluated, e.g., NMR, [1,2,3], infrared, [4], UV/Vis, [5] or x-ray diffraction. [6,7,8] First-row transition metal systems, with their near-degenerate 3d electron levels, are prominent examples of systems with close-lying electronic states. This can lead to difficulties in calculating both electronic ground states and reaction pathways.…”
Section: Introductionmentioning
confidence: 99%